Implications of the Inability to Pay Iddah Maintenance and Madiyah Maintenance in the Case of a Petition for Divorce (Analysis of PERMA No.3 of 2017 and SEMA No. 2 of 2019) - Al-Umam Sitepu, Sayyid; Lubis, Fauziah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The purpose of this paper is to evaluate the direct implications for women, especially wives, if their rights in divorce are not fulfilled. This evaluation is based on the principle that women have equal rights under the law, as regulated in SEMA No. 2 of 2019 concerning the protection of women in the legal system. This research will explain in detail the implications for women if they do not obtain their rights after divorce, such as iddah maintenance and madhiyah maintenance in cases of contested divorce. The study employs a qualitative method with an empirical juridical approach. Primary data sources include interviews with legal experts and affected individuals, while secondary data sources encompass relevant legal documents and literature. The conclusion of this research is that women have the right to obtain their rights after divorce, including iddah and madhiyah maintenance, even in cases of contested divorce, in accordance with the relevant SEMA. Failure to obtain these rights results in various legal and negative implications for women, both long and short term.